Título Padrão - Pepis Belinelli, Gabriela; Merlin Deganutti de Barros, Eliana; Lopes Cristovão, Vera Lúcia (Revista de Letras, 2022)
The data analyzed in this article were generated by a virtual teacher education sequence (SVFD) implemented as part of a master's research and directed to Portuguese Language teachers of Basic Education. The focus of the course was teaching the genre 'opinion article' through the procedure 'didactic sequence of genres' (SDG) systematized by researchers of Sociodiscursive Interactionism (ISD). This work aims to analyze the conception of the teacher-course participants concerning the SDG before and after the formative process, using two questionnaires applied during the course, one initial and one final, based on a specific question about the SDG. The theoretical and methodological basis of the research is ISD, and mainly the studies focused on language didacticism. The analyses show that the SVFD caused changes in the conception of most teachers once they began to understand SDG based on its theoretical and methodological foundations.